Refund of the balance in favor of the exporter and exports of metallic minerals from the Peruvian mining sector - Levano Huamaccto, Ronald Studer (2022)
Objective: To determine the association between the refund of the exporter's credit balance and the exports of metallic minerals of the Peruvian mining sector during the period 2005-2021. Method: The approach was quantitative, the design was observational, cross-sectional, retrospective, and analytical; the level was correlational. The Shapiro-Wilk normality test was applied to determine if the data corresponds to a normal distribution; additionally, hypothesis tests were used to determine the relation between the study variables. Result: There is an average positive correlation between the refund of the exporter's credit balance and the Peruvian mining sector's exports of metallic minerals, with a degree of correlation of +0,665. Conclusion: The refund of the exporter's credit balance is related to the exports of metallic minerals from the Peruvian mining sector during the period 2005-2021.